Content appraisal and age moderate the relationship between passive social media use and mental ill-being - Evans, Olivia; Hardacre, Stephanie; Rubin, Mark; Tran, Max (Frontiers in Psychology, 2023)
An important distinction to make when assessing the impact of social media use on mental health is whether the use is passive (e.g., browsing) or active (e.g., posting). Recent research suggests that the connection between passive social media use and mental ill-being is inconsistent, with some research finding a significant negative association, while other research finds no such association. In the present research, we sought to investigate this relationship, as well as two potential moderators of this relationship: the subjective appraisal of social media content social media users consume (i.e., positively or negatively-appraised) and age of users. In a cross-sectional survey of Australian and United States Facebook users (N = 991), there was no direct relationship between passive use and mental ill-being, however user age and positive (but not negative) content appraisal were found to moderate the relationship between passive use and mental ill-being. Specifically, the relationship between passive use and mental ill-being became weaker as subjective positive appraisal increased, and it reversed to become negative at high levels of positive appraisal. Additionally, the positive relationship between passive use and mental ill-being became weaker as age of social media users increased, and the direction of this relationship became negative at the oldest ages of social media users. These results suggest that the relationship between social media use and mental ill-being is more nuanced than previous research suggests. In particular, higher amounts of passive Facebook use may have a less negative, or even a positive effect on social media users’ mental health when the content being (passively) consumed is positively appraised, or when users are older.